Development and Validation of a New Analytical HPLC-PDA Method for Simultaneous Determination of Cucurbitacins B and D from the Roots of Trichosanthes kirilowii - Kim, Hyoung Ja; Lee, Jae Yeol; Cheon, Chunhoo; Ko, Seong-Gyu (Hindawi Publishing Corporation, 2022)
Trichosanthes kirilowii, one of the herbal formulas named SH003, has been used for treatment in traditional medicine. This paper aimed to analyze the marker compounds from the roots of T. kirilowii and evaluate a validation method for cucurbitacins B and D using high-performance liquid chromatography-photodiode array detector (HPLC-PDA). Two marker compounds were identified as cucurbitacin B (1) and cucurbitacin D (2) from the roots of T. kirilowii by spectroscopic analyses. Cucurbitacins B and D peaks were well separated and were detected at 15.4？min and 12.4？min, respectively, by a UV detector at 230？nm with the linearity (R2？>？0.999) range between 5 and 250？μg/mL, limit of detections (LODs) were 1.87？μg/mL and 1.30？μg/mL, respectively, while limit of quantifications (LOQs) were 5.66？μg/mL and 3.93？μg/mL, respectively. The established method offered good precision with overall intra- and inter-day variations of 0.34？1.26 and 0.26？1.35%, respectively, for % relative standard deviation (RSD, acceptance limit %RSD <3%). The cucurbitacins B and D recoveries ranged from 99.2 to 101.7% and 98.6 to 102.0%, respectively. These results suggest that cucurbitacins B and D could be a valuable candidate for marker compounds of the extract from T. kirilowii, and the proposed method was shown applicability for quality control of SH003.